Polymorphic phase transition in BaTiO3 by Ni doping. Issue 13 (September 2019) - Duong, Nguyen Xuan; Bae, Jong-Seong; Jeon, Jongchul; Lim, So Yeon; Oh, Soo Han; Ullah, Aman; Sheeraz, Muhammad; San Choi, Jin; Ko, Jae-Hyeon; Yang, Sang Mo; Kim, Kyou-Hyun; Kim, Ill Won; et al.
Abstract: We demonstrate a phase transition between BaTiO3 polymorphs induced by Ni substitution experimentally. The structural evolution of tetragonal-to-hexagonal polymorph in Ni-doped BaTiO3 ceramics is observed macroscopically and then, visualized in an atomic scale. Under this structural transition, the long-range ferroelectric ordering in the undoped BaTiO3 with tetragonal symmetry is suppressed and eventually, vanishes in the heavily Ni-doped BaTiO3 with hexagonal symmetry and dielectricity. An oxygen vacancy defect can be created at a local Ni doping site with a decrease in the charge valence state from Ti 4+ (3 d 0 ) to Ti 3+ (3 d 1 ). With the reduction of the Ti 4+ oxidation state, the polar Ti–O ionic displacement is degenerated in the tetragonal BaTiO3 and thereby, the short-range Coulomb repulsion may be restored in the hexagonal BaTiO3 resulting in a polymorphic phase transition. Our work is of potential interest for artificial realization of an exotic phase in complex oxide materials by doping.